Analisis Dinamika Budaya Senioritas di Lingkungan Pendidikan - Khairunniza, Liza; Eftiza Khairunniza, Liza Dwi; Supriatna, Nana (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
Seniority culture in educational settings reflects social hierarchies based on age, level, or experience differences. This study examines how conflict dynamics between senior and junior groups in a seniority-based educational environment affect students' social interactions and foster a safe, inclusive atmosphere. Using a literature review method, the research employs conflict theory to understand seniority culture dynamics, involving literature search, selection, systematic data organization, analysis of findings, and synthesis. The findings indicate that seniority culture can influence students' social interactions, often leading to negative behaviors such as bullying and discrimination. Family, school, and community environments significantly shape students' behavior related to seniority, with a lack of social control triggering negative behaviors. Recommendations include changing values, enhancing moral education, and increasing the role of teachers and school staff in cultivating a safe, inclusive environment. The research underscores the need for awareness of seniority culture's impact and implementing concrete measures to mitigate its negative effects. Implications emphasize value transformation, the crucial role of educators, and collaboration between family, school, and community to foster effective social control. This study offers a comprehensive understanding of seniority culture in education and highlights the importance of collective efforts to create safe and inclusive educational environments